Neoclassical Growth and the Efficient Program of Capital Accumulation - Atsumi, Hiroshi (Review of Economic Studies, 1965)
Journal Article Neoclassical Growth and the Efficient Program of Capital Accumulation Get access Hiroshi Atsumi Hiroshi Atsumi Rochester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 2, April 1965, Pages 127–136, https://doi.org/10.2307/2296057 Published: 01 April 1965